Anophthalmia and Microphthalmia in Pakistan: Current Genetic Insights and Future Perspectives - Hameed, Usman; Saleem, Ammara; Idrees, Memoona; Ansar, Muhammad (Current Trends in OMICS, 2025)
Anophthalmia and microphthalmia (A/M) are genetic disorders characterized by the absence or reduced size of the ocular globe, as compared to the globe size of the normal population. These disorders can be inherited in both autosomal recessive and dominant patterns. Certain genes have been reported to contribute significantly to the emergence of diseased phenotypes. Mutation in Forkhead Box E3 gene has been reported in different studies involving the Pakistani population, where the pattern of inheritance is autosomal recessive. Moreover, ALDH1A3 and VSX2 have been associated as well with severe phenotypes of A/M. SOX2 has been reported in the cases of de novo mutations and syndromic microphthalmia. The current review summarizes the most recurrent mutations in these genes in patients suffering from A/M in Pakistan. It showcases the importance of variant studies and how the demographic location of individuals may make them susceptible to a particular type of mutation. It also compares mutation profiles between the Pakistani population and global cohorts, emphasizing the impact of consanguineous marriages on the high prevalence of these conditions in the country. More studies may prove helpful in formulating a diagnostic kit for this disease so that a genotype-phenotype correlation can be established.